Near-Infrared Light-Triggered Photodynamic Therapy and Apoptosis Using Upconversion Nanoparticles With Dual Photosensitizers - Lee, Song Yeul; Lee, Ruda; Kim, Eunha; Lee, Sanghee; Park, Yong Il (Frontiers in Bioengineering and Biotechnology, 2020)
Elucidation of upconversion nanoparticles (UCNPs) that can be excited by near-infrared (NIR) light is an interesting topic in the field of photodynamic therapy (PDT). However, the PDT efficiency of conventional UCNPs is limited due to the low quantum yield and overheating effect of the 980 nm light source. In this study, a light source with a wavelength of 808 nm was used as an excitation source for Nd-doped UCNPs to solve the overheating effect. UCNPs with a core@shell structure (NaYF4:Yb,Er,Nd@NaYF4:Yb,Nd) were synthesized to increase the upconversion emission efficiency. Dual-color emitting Er-doped UCNPs and dual photosensitizers (Chlorin e6 and Rose Bengal) were used for enhanced PDT. Each photosensitizer could absorb red and green emissions of the UCNPs to generate reactive oxygen species (ROS), respectively. The ROS generation in a dual photosensitizer system is significantly higher than that in a single photosensitizer system. Additionally, PDT induces immunogenic apoptosis. In this study, by utilizing a highly efficient PDT agent, PDT-induced apoptosis was studied by biomarker analysis.